PENGALAMAN GAYA KOMUNIKASI KEPEMIMPINAN PEREMPUAN DI ORGANISASI KEMAHASISWAAN UPN "VETERAN" JAKARTA - Nikmat Rizal Mubarok (2021)
Based on observations in recent years, the leadership of a female leader has begun to emerge and is increasingly widespread, in her leadership the female leader also applies her own leadership communication style. Quoted from Idntimes.com (2020) according to the news in the eyes of the community, in an organization or institution, a woman's leadership communication style is identified as more structured and disciplined, but not all female leaders apply such a leadership communication style. The purpose of this study was to determine the meaning and experience of women's leadership communication styles in the student organization of UPN "Veteran" Jakarta. The urgency of the research focuses on the benefits of stories from the experiences of women leaders in applying their leadership communication styles for prospective leaders and members of an organization. This research method used is a qualitative approach to applied phenomenology by analyzing research data based on the experiences of the informants and correlated with the concepts that have been selected in the study. The data analysis technique used is purposive sampling technique to take samples. After searching based on the criteria, obtained as many as 8 informants. Then an online interview was conducted, and based on the results of the interview the data was then analyzed in the discussion section, then the data validity was then carried out using member checks. The results of this study found the meanings, experiences, and themes of women's leadership communication styles including: leadership communication style adapting, neat and structured, communication on target, message effectiveness based on situation, problem solving more orderly and orderly, theme depending on the situation organization.